Long road : Pearl Jam and the soundtrack of a generation - Hyden, Steven, 1977- (Hachette Books, Hachette Book Group, 2022)
"Ever since Pearl Jam first blasted onto the Seattle grunge scene three decades ago with their debut album, Ten, they have sold 85M plus albums, performed for hundreds of thousands of fans around the world, and have even been inducted into the Rock and Roll Hall of Fame. In Long Road: Pearl Jam and the Soundtrack Of A Generation, music critic and journalist Steven Hyden celebrates the life, career, and music of this legendary group, widely considered to be one of the greatest American rock bands of all time. Long Road will be structured like a mix tape, using 20 different Pearl Jam classics as starting points for telling a mix of personal and universal stories. Each chapter will tell the tale of this great band; how they got to where they are, what drove them to greatness, and why it matters now. Much like the generation it emerged from, Pearl Jam is a mass of contradictions. They were an enormously successful mainstream rock band who felt deeply uncomfortable with the pursuit of capitalistic spoils. They were progressive activists who spoke in favor of abortion rights and against the Ticketmaster monopoly, and yet they epitomized the sound of traditional, male-dominated rock 'n' roll. They were looked at as spokesmen for their generation, even though they ultimately projected profound confusion and alienation. They triumphed, and failed, in equal doses - the quintessential Gen-X tale. Impressive as their stats, accolades, and longevity may be, Hyden also argues that Pearl Jam's most definitive accomplishment lies in the impact their music had on Generation X as a whole. Pearl Jam's music helped an entire generation of listeners connect with the glory of bygone rock mythology, and made it relevant during a period in which tremendous American economic prosperity belied a darkness at the heart of American youth. More than just a chronicle of the band's career, this book will also be a story about Gen- X itself, who like Pearl Jam came from angsty, outspoken roots and then evolved into an establishment institution, without ever fully shaking off their uncertain, outsider past. For so many Gen-Xers growing up at the time, Pearl Jam's music was a beacon that offered both solace and guidance. They taught an entire generation how to grow up without losing the purest and most essential parts of themselves. Written with his celebrated blend of personal memoir, criticism, and journalism, Hyden explores Pearl Jam's path from Ten to now. It will be a chance for new fans and old fans alike to geek out over Pearl Jam minutia-the B-sides, the beloved deep cuts, the concert bootlegs-and explore the multitude of reasons why Pearl Jam's music resonated with so many people. As Hyden explains, "Most songs pass through our lives and are swiftly forgotten. But Pearl Jam is forever.""--Provided by publisher.